Marketing Strategies in Delivering Customer Satisfaction: A case study of Nestlé - Chang, Poh Lin; Chang, Ying Ying; Chinnappan, Celine Cassandra A/P; Chai, Ming Hao; Ladeuth, Luisa María Arrieta (AIBPM Publisher, 2023)
The success of a business depends on its use of marketing methods. Nestlé will always be prepared with comprehensive strategies to open a broader market to obtain customer satisfaction. This research aims to investigate the relationship between 4Ps marketing strategies including product, price, place, and promotion strategy with customer’ satisfaction. A total number of one hundred and sixty respondents who are Nestlé users participated in the survey to acknowledge whether those marketing strategies significantly affect customer satisfaction. Multiple linear regression was used to conduct hypothesis tests. The findings reveal that all elements of marketing strategies were significantly related to customer satisfaction. This research will provide some suggestions to increase Nestlé 's reputation and their customer satisfaction.